A diagnostic dilemma of two rare stroke mimics in a pediatric patient - Chencheri, Nidheesh Cheeyancheri; Kashyape, Pawan Subhash; Khamis, Sonia; Elamin Agna, Maha Mohammed (International Journal of Contemporary Pediatrics, 2017)
A seven and half year-old male patient presented with clinical symptoms suggestive of stroke. However, the MRI showed atypical lesions in non-vascular distribution and with varying ages. This led to extensive investigations, which suggested a differential diagnosis of CNS neurosarcoidosis and primary CNS vasculitis. Both these are exceedingly rare conditions needing tissue diagnosis and prolonged immunosuppression